2021
DOI: 10.1021/acs.jpcc.1c10037
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Supramolecular Inclusion Complexes of β-Cyclodextrin with Carboxyphenyl Viologens Showing Photochromic Properties

Abstract: β-Cyclodextrins (β-CDs) are shown to form 1:1 and 2:1 host−guest inclusion complexes with two carboxyphenyl viologens, 1-(4-carboxyphenyl)-4,4′-bipyridinium chloride (1 + • Cl − ) and 1,1′-bis(4-carboxyphenyl)-4,4′-bipyridinium dichloride (2 2+ •Cl 2 − ), in an aqueous solution. The solid-state supramolecular host−guest inclusion complexes 1 + @β-CD and 2 2+ @β-CD 2 demonstrate excellent photochromic properties. The results of the electron-spin resonance (ESR) spectroscopy suggest that their photochromic behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
(67 reference statements)
0
19
0
Order By: Relevance
“…In addition, this mixed matrix film also has good ductility, which makes us believe that the application prospect of M −1 device in the field of UV detection is very broad (Figure 11e). In 2022, Liu′s group also reported two viologen‐based compounds with excellent photochromic ability [107] . Under the irradiation of 300 W Xe lamp, both 1 + @β‐CD and 2 2+ @β‐CD 2 were found to have similar photochromic behaviors, and the color change of 1 + @β‐CD was from gray white to dark blue, and surprisingly it was found that the color change was basically saturated within 3 min (Figure 11f).…”
Section: Chromismmentioning
confidence: 88%
See 4 more Smart Citations
“…In addition, this mixed matrix film also has good ductility, which makes us believe that the application prospect of M −1 device in the field of UV detection is very broad (Figure 11e). In 2022, Liu′s group also reported two viologen‐based compounds with excellent photochromic ability [107] . Under the irradiation of 300 W Xe lamp, both 1 + @β‐CD and 2 2+ @β‐CD 2 were found to have similar photochromic behaviors, and the color change of 1 + @β‐CD was from gray white to dark blue, and surprisingly it was found that the color change was basically saturated within 3 min (Figure 11f).…”
Section: Chromismmentioning
confidence: 88%
“…(g) Erasable inkless printing on the 1 + @β‐CD‐coated filter paper [107] . (h) QR code recognized by a smartphone [107] . (i–j) UV‐Vis spectra of compound 1 under a Xe lamp or blue ray.…”
Section: Chromismmentioning
confidence: 99%
See 3 more Smart Citations